IMPLEMENTASI REKOMENDASI FINANCIAL ACTION TASK FORCE (FATF) TERHADAP KEJAHATAN PENCUCIAN UANG DI INDONESIA - Octaviani, Beutari; Susitianingsih, Hermini; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Money laundering is an act of crime that can destabilize theeconomical condition of a country. Vienna Convention in 1988,which examine about drugs, is the basis of discussion on anti-moneylaundering regime. International response for the fighting againstmoney laundering is by establishing FATF. FATF has severalrecommendations which are admitted as the international standards.In its framework, FATF have a black list system that providesoverview on the countries that do not take part in the fight againstmoney laundering. Indonesia is not a member of FATF, but waslisted in FATF’s black list system in 2000. This research aims to findout the causes of FATF recommendation implementation byIndonesia. Descriptive type of research is applied in this research todescribe the process that Indonesia has gone through in fightingagainst money laundering by implementing FATF recommendation.The result of this research shows Indonesia’s serious effort incombating money laundering.